New Business and Regulatory Strategies in the Postal Sector (Topics in Regulatory Economics and Policy, 2018)
This book addresses major issues facing postal and delivery services throughout the world. Worldwide, there is currently a considerable amount of interest in postal and delivery economics. The industry is reacting to a state of near crisis and is implementing different drastic changes. The European Commission and member States are still wrestling with the problem of how to implement entry liberalization into postal markets, how to address digital competition, and how to maintain the universal service obligation (USO). The Postal Accountability and Enhancement Act of 2006 in the U.S. has perhaps created and exacerbated the problems faced by USPS. Digitalisation, technological development and online platforms are strongly affecting both the way postal and delivery operators are managing their services as well as their role on the market. Strong emphasis was attributed to the assets of Postal Operators (POs) and their added value in the digital age as well as on new business strategies. This volume presents original essays by prominent researchers in the field, selected and edited from papers presented at this year's 26th Conference on Postal and Delivery Economics held in Split, Croatia, from May 30- June 2, 2018.Topics addressed by this volume include quality of service, last mile solutions, and competition in the liberalized market. This book will be a useful tool not only for graduate students and professors, but also for postal administrations, consulting firms, and federal government departments. .